Pengaruh Latihan Fisik Dan Respon Molekuler Pembuluh Darah Arteri - Dyana Sarvasti; Basuni Radi; Budhi Setianto; Andang H Joesoef (The Indonesian Heart Association, 2011)
Regular physical activity (exercise training, ET) has a strong positive link with cardiovascular health. The beneficial effects of ET on the endothelium arteries are believed to result from increased vascular shear stress during ET bouts. A number of mechanosensory mechanisms have been elucidated that may contribute to the effects of ET on vascular function. Exercise training also consistently improves the nitric oxide bioavailability, and the number of endothelial progenitor cells, and diminishes the level of inflammatory markers, namely pro inflammatory cytokines and C-reactive protein. This review summarizes current understanding of control of vascular adaptation by exercise and how these processes lead to improved cardiovascular health.